COMPLEX EVALUATION MODEL OF A SMALL-SCALE PHOTOVOLTAIC INSTALLATION PROFITABILITY (ETIMA, 2021)
Abstract: Number of small-scale photovoltaic installations grows rapidly every year. A decade ago,this was motivated solely by the attempt to reduce greenhouse gas emissions, because the investment itselfwas not economically viable. Nowadays, the table is turning. Small-scale installations are becomingprofitable, if selected wisely. Therefore, the article discusses, what are the factors that need to be taken intoconsideration when selecting the photovoltaic installation, what data must be collected beforehand and howto proceed in their analysis. To sum up, the article provides an in-depth methodology for the small-scalephotovoltaic installation assessment that is aimed to be used in household's or small commercial consumer'sprofitability appraisal of such an investment.Keywords— photovoltaic systems; profitability; price; electricity consumption; electricity generation;renewable energy sources support; energy storage; optimization; standard consumption diagram